The Effect of Competency and Work Experience on the Performance of Teaching Staff at SPN Polda Metro Jaya - Disca Cris Faratih; Harries Madiistriyatno; Widya Nengsih (Dinasti Publisher, 2026)
The performance of teaching staff is a strategic factor in supporting the success of the education and training process at the National Police School (SPN) of the Jakarta Metropolitan Police. Teaching staff with high competence and adequate work experience are expected to be able to deliver learning materials effectively, professionally, and in accordance with the demands of police duties. This study aims to analyze the influence of competence and work experience on the performance of teaching staff at the SPN of the Jakarta Metropolitan Police, both partially and simultaneously. This study uses a quantitative approach with a survey method. The study population was 132 teaching staff, with a sample of 99 respondents determined using a specific sampling technique. Data collection was carried out through questionnaires, while data analysis used multiple linear regression with the help of the SPSS program. The results of the study indicate that partially, competence has a positive and significant effect on teaching staff performance. This finding indicates that the higher the level of competence of teaching staff, the higher the resulting performance. In addition, work experience also has a positive and significant effect on teaching staff performance, indicating that the length of experience and mastery of tasks obtained from work practices contribute significantly to improving performance. Simultaneously, competence and work experience have a significant effect on teaching staff performance. The coefficient of determination (R Square) value of 0.442 indicates that competence and work experience are able to explain 44.2% of the variation in teaching staff performance, while the remaining 55.8% is influenced by other factors outside the research model. This study confirms that continuous improvement of competence and strengthening of work experience are important factors in improving the performance of teaching staff in the SPN Polda Metro Jaya environment